Does digital finance impact debt concentration of Chinese firms?. Issue 7 (16th April 2023) - Chen, Caiyun; Li, Minghuan
ABSTRACT: We investigate the relation between digital finance and debt concentration in capital structures of firms. Measuring digital finance with a comprehensive index, we show that digital finance is indeed related to more concentrated debt structures of firms. Turning to the sub-indices of digital finance, coverage breadth and usage depth of digital finance increase firms' debt concentration, while digitization degree is not a central concern for firms. The link between digital finance and debt concentration is stronger for companies with high level of information asymmetry and high default risk.